Philosophical Study of Islamic Economics: Theological and Empirical Perspectives - Sinollah, Sinollah; Bisri, Hasan; Adam, Saed M (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
Islamic economics is fundamentally rooted in divine principles, shaping an economic system that originates from God, is directed towards God, and operates within the framework of Sharia law. Unlike conventional economic systems, which often prioritise materialism and individualism, Islamic economics integrates moral and ethical values, ensuring economic justice and social welfare. The system is built upon two key arguments: first, a theological foundation that emphasises divine guidance in economic activities, and second, an empirical and philosophical perspective that addresses real-world economic challenges. This study examines the philosophical underpinnings of Islamic economics, contrasting it with capitalist and socialist ideologies, which often fail to resolve socio-economic inequalities. By incorporating principles of fairness (ʿadl) and balance (tawāzun), Islamic economics provides an alternative framework that prioritises collective well-being. The study further explores the implications of Islamic economic thought on contemporary financial practices, highlighting its relevance in fostering ethical and sustainable economic growth